KNOWLEDGE IN LITERARY HERITAGE OF ATABETU’L HAKAYIK AND ABAY KUNANBAYEV - Ozan GÖKDEMİR (Fırat University, 2020)
The subject of Atibetü’l-Hakāyık, by Edib Ahmed YÜKneki, is generally composed of the rules of religion and ethics. In the work, it is stated that the recognition of the world, god and man will be through science and gives advice on many issues such as the benefit of knowledge and the harm of ignorance. Abay Kunanbayev is one of the most important figures of Kazakh and Turkish literature in the XIXth century. Science and knowledge play an important role in Abay's literary heritage. According to Abay, ignorance is the main source of injustice, civilization, self-praise, inability to attract each other, lies, gossip and laziness. For this reason, Abay emphasized the importance of knowledge, education and science in his works. Abay defends that the main skill is to bring the mind, effort and heart together, and that only science can bring these three together. In this study, knowledge and science in the poems of two important figures of Turkic World Literature was examined. The importance of concepts such as mind, knowledge and science in the cultural memory of the Turkish nation has been revealed through the works written in different periods and fields.